The Leadership Of The Kiai In The Moral Guidance Of Students At Islamic Boarding Schools - Syarif Ali Alqadrie; Asmawati Mahidi (IJIBS, 2025)
This study examines the leadership of kiai in fostering the character of santri at the Al Mubarok Miftahul Ulum Islamic Boarding School as a central mechanism for character building through the integration of managerial, cultural, and spiritual functions. This study departs from the finding that kiai not only play a role as managers of educational institutions, but also as moral authorities who set standards of behavior, value expectations, and character-based educational practices in the daily lives of santri. The research uses a qualitative approach with a descriptive design. The research subjects were selected purposively, including kiai, teachers, and santri. Data were collected through in depth interviews, participatory observation of religious and learning activities, and documentation of the pesantren's programs and rules. The results show that the kiai leadership model is formed from a combination of personality, religious authority, knowledge, and leadership experience, which is manifested in continuous supervision, exemplary behavior (Ibda' bi Nafsik), religious habits, and competency based task distribution. This pattern reflects the integration of contingency, transformational, religious, and path-goal leadership applied contextually through democratic, firm, and supportive styles. Routine worship, moral advice, and daily discipline reinforce the internalization of values until they become habits of the santri.